Translation, Adaptation, and Validation of Revised Colorectal Cancer Perception and Screening Instrument among First-Degree Relatives of People with Colorectal Cancer in China - Yang Bai; Winnie K W. So; Cho Lee Wong (Elsevier, 2020)
Objective: The purpose of the study was to translate and validate the psychometric properties of the Revised Colorectal Cancer Perception and Screening (RCRCPS) instrument for the first-degree relatives (FDRs) of people with colorectal cancer (CRC) in China. Methods: The translation, adaptation, and validation guideline developed by Sousa and Rojjanasrirat was used to guide this study. All items from the Colorectal Cancer Perception and Screening (CRCPS) instrument and three items from the Perceived Barriers Questionnaire were combined and further adapted for a colonoscopy test, resulting in RCRCPS. The resultant RCRCPS was translated from English to Chinese through forward- and backward-translation methods, and a panel review was conducted to examine its content validity. The RCRCPS (simplified Chinese version) was then tested with a convenience sample of 197 Chinese FDRs of patients with CRC. Validity was tested through confirmatory factor analysis (CFA) and discriminative validity, and reliability was assessed using Cronbach's α and test-retest reliability. Results: The content validity index (CVI) of the RCRCPS (simplified Chinese version) was satisfactory (item CVI = 0.80-1 and scale CVI = 0.92). The results demonstrated acceptable internal consistency (Cronbach's α = 0.74-0.87) and test-retest reliability in a 4-week interval (intraclass coefficient = 0.53-0.84). CFA revealed that the RCRCPS (simplified Chinese version) conformed to the four-factor model suggested by the original version (Chi-square/degree of freedom = 1.326, root-mean-square error of approximation = 0.041, comparative fit index = 0.904, Tucker-Lewis index = 0.896, and standardized root mean square residual = 0.684). Conclusions: The 38-item simplified Chinese version of RCRCPS demonstrated acceptable reliability and validity. Healthcare professionals may use this instrument in the development and evaluation of interventions to promote colonoscopy screening among people at an increased risk of developing CRC.